Francysk Skaryna as the founder of the Old Belarusian editing - Zhauniarovich, Piotr P. (Journal of the Belarusian State University. Journalism, 2021)
The features of Old Belarusian editing are discussed on the example of the editorial activity of Francysk Skaryna in the period of 1517–1525. It is noted that the Belarusian first printer originatively mastered the techniques of creating a handwritten book developed over the centuries, which was widely distributed in the Belarusian lands. Attention is focused on the new approaches of F. Skaryna in the design of the title page, the creation of forewords and afterwords, in the introduction to the printed book of glosses and annotation elements. The translation of the texts of Holy Writ into the Old Belarusian language and their editorial processing became obligatory in the conditions of the Belarusian Renaissance, the voice and acting representative of which was F. Skaryna. Approaching of canonical texts to the perception of the common man, who learned from the biblical books, is the main editorial tactic of the first printer in the overall strategy of publishing «To God for worship and common people to good learning».
Keywords: history of Belarusian editing; Francysk Skaryna; title page; foreword; afterword; annotation; glosses